Analisis Karya Seni Grafis “Thirteen Lights” Menggunakan Metode Kritik Seni Feldman - Tatiana Helga Alrifzkha; Dyah Yuni Kurniawati (Penerbit dan Percetakan, CV. Picmotiv, 2026)
The phenomenon of Korean Pop (K-Pop) has had a major influence on the development of visual culture and the creativity of younger generations, including in the creation of artworks. Artists’ interest in popular culture can become a source of inspiration in producing artworks that contain aesthetic value and social messages. This study aims to analyze a high-relief printmaking artwork entitled Thirteen Lights using Edmund Burke Feldman’s art criticism method. The artwork was inspired by the South Korean boy group Seventeen, which represents togetherness, solidarity, and mutual support among its members. The study employed a descriptive qualitative method through the stages of description, formal analysis, interpretation, and evaluation. The results show that the artwork possesses strong visual qualities through a centralized composition, expressive lines, contrasting colors, and visual symbols that create a dynamic impression. The artwork represents togetherness, solidarity, and collective support in the lives of young people inspired by Korean popular culture. The artwork not only has aesthetic value but also reflects the influence of the Korean Wave on the development of contemporary visual art. This study is expected to serve as a reference for the analysis of artworks inspired by popular culture.